Effects of miR-7 on Hcy-induced rat cerebral arterial vascular smooth muscle cell proliferation, migration and inflammatory factor expression by targeting MMP-14 to regulate TLR4/NF-ÎºB signaling pathway - Ma, Hongdan; Wang, Lei; Lv, Wen; Lv, Zheng (Cellular and Molecular Biology, 2020)
The current research aimed to investigate the effect of miR-7 targeting matrix metalloproteinase 14 (MMP-14) on homocysteine (Hcy)-induced rat cerebral artery vascular smooth muscle cells (VSMCs) proliferation, migration and inflammatory factor expression and its possible mechanism. The expression of miR-7 and MMP-14 in Hcy-induced VSMCs were detected by real-time fluorescent quantitative PCR (RT-qPCR) and Western blot. Methyl Thiazolyl Tetrazolium (MTT) method, Transwell assays and enzyme-linked immunosorbent assay (ELISA) were performed to detect the effect of miR-7 and MMP-14 expression on the proliferation and migration, as well as interleukin 6 (IL-6) and tumor necrosis factor É‘ (TNF-É‘) expression of Hcy-induced VSMCs. The interaction between miR-7 and MMP-14 was detected by dual-luciferase reporter gene assay. Western blot was applied to analyse the effects of miR-7 and MMP-14 expression on the Toll-like receptor (TLR4)/nuclear transcription factor-KB (NF-ÎºB) signaling pathway. The results showed that after induced by Hcy, the expression of miR-7 in VSMCs was significantly reduced, the expression of MMP-14 was significantly increased, and the cell viability, the number of migrating cells, IL-6 and TNF-É‘ expression were significantly increased (P<0.05). After overexpression of miR-7, the viability, migration cell numbers, IL-6 and TNF-É‘ expression of Hcy-induced VSMCs were significantly reduced (P<0.05). miR-7 directly binds to MMP-14 and negatively regulates the expression of MMP-14. After overexpression of miR-7, the levels of TLR4 and p-NF-ÎºB p65 in VSMCs were significantly reduced (P<0.05); overexpression of MMP-14 could reduce the effect of miR-7 overexpression on TLR4 and p-NF-ÎºB p65 expression in VSMCs (P<0.05). Overexpression of MMP-14 and/or activation of the TLR4/NF-ÎºB signaling pathway could reverse the effect of miR-7 overexpression on the proliferation, migration and IL-6 and TNF-É‘ expression of Hcy-induced VSMCs (P<0.05). It is concluded that miR-7 can inhibit Hcy-induced rat cerebral artery VSMCs proliferation, migration, and inflammatory factor expression by targeting the regulation of MMP-14 expression and inhibiting the activation of the TLR4/NF-ÎºB signaling pathway.